Baby driver [videorecording (DVD)] - Wright, Edgar, 1974-; Elgort, Ansel, 1994-; Spacey, Kevin; James, Lily, 1989- (Sony Pictures Home Entertainment, 2017)
When a getaway driver is persuaded into working for a crime boss, he finds himself partaking in an operation that is doomed to fail.